Serum globulin levels are associated with HIV reservoir size and immune restoration during long‐term ART. Issue 3 (13th September 2022) - Zhang, Qing; Jiao, Yan‐Mei; Li, Guang; Zhang, Lu‐Xue; Gao, Lin; Guo, Xiao‐Yan; Mijiti, Zilaiguli; Guo, Yun‐Tian; Xu, Wen; Huang, Hui‐Huang; Wang, Fu‐Sheng
Abstract: Objectives: The objectives of this study were to analyze the relationship between serum globulin levels and immune restoration and HIV reservoir size during long‐term antiretroviral therapy (ART). Methods: We enrolled 13 patients living with HIV who had been receiving ART for 5 years. We measured levels of serum globulin, cell‐associated (CA) HIV DNA and RNA, and p24 antibody at 0, 1, 3, and 5 years of ART. CD38 and human leukocyte antigen – DR isotype (HLA‐DR) were used as activation markers for T‐cell activation. Serum concentrations of the inflammatory cytokines interferon gamma‐inducible protein (IP)‐10 and soluble CD163 (sCD163) were detected by enzyme‐linked immunosorbent assay. We analyzed the relationship between serum globulin levels, HIV reservoir size, immune restoration, T‐cell immune activation, and inflammatory levels during long‐term ART. Results: Our data showed that serum globulin levels in people living with HIV were higher than in healthy controls and significantly decreased during the first year of ART. Serum globulin levels during long‐term ART were positively correlated with CA HIV DNA, CA HIV RNA, p24 antibody levels, and CD8 + T‐cell counts and negatively correlated with CD4 + T‐cell counts and CD4/CD8 ratios. Moreover, serum globulin levels were positively correlated with CD4 + and CD8 + T‐cell activation and the concentrations of inflammatory biomarkers IP‐10 and sCD163 during long‐term ART. Conclusions: Our findings suggest that serum globulin levels may be associated with HIV reservoir size and immune restoration during long‐term ART.